Towards a living agriculture: extension of the notion of agriculture among rural extension agents based on a comprehensive approach to indigenous knowledge in Caldas, Colombia - Sastoque, Marlon Javier Méndez (Revista de Economia e Sociologia Rural, 2022)
Agriculture as a business remains the dominant notion among agronomists that work as rural extension agents. Following this vision, their main contribution is to transfer the technical–scientific knowledge for manipulating natural environments to maximize the yield of the communities of cultivated plants. However, it is considered that contrasting one's ideas with those of others -in this case native communities- allows us to recognize, reflexively, the preconceptions themselves. In this framework, the objective of the investigation was to determine how the dominant point of view among agronomists educated within the technical–scientific paradigm changes upon comprehensive interaction with the traditional knowledge. Results derive from analyzing the interviews of rural extension agents who offer their services to native communities in Caldas, Colombia. From the analyses, it can be concluded that, nowadays, agronomists more easily understand that in the local context, agriculture, rather than a business, is a life-producing activity; that elements of nature are subjects that interact and coexist around the reproduction of life rather than objects to manipulate and appropriate; that, in practice, the scientific knowledge adopted is blended with traditional and mystic knowledge, thereby creating a multicultural conservationist practice. Resumo: A agricultura vista como um agronegócio continua a ser a noção dominante entre os agrônomos que trabalham como extensionistas rurais. Guiados por essa visão, transferir conhecimentos técnico-científicos para manipular o ambiente natural, a fim de maximizar o desempenho das comunidades de plantas cultivadas, é sua principal contribuição. No entanto, supõe-se que confrontar dita visão com a de outros sujeitos, neste caso membros de comunidades indígena-camponesas, lhes permite questionar, reflexivamente, os próprios preconceitos. Nesse contexto, a pesquisa visou indagar como essa visão dominante entre os agrônomos formados no paradigma técnico-científico muda ao entrar compreensivamente em contato com o conhecimento tradicional. Os resultados derivam da análise de entrevistas com extensionistas rurais que prestam serviços a comunidades indígenas no departamento de Caldas, Colômbia. Conclui-se que os agrônomos consultados com mais facilidade hoje entendem que, no contexto local, a agricultura, mais do que um negócio, é uma atividade produtora de vida. Que os elementos da natureza, em vez de objetos manipuláveis e apropriáveis, são sujeitos com os quais se interage e coexistem em torno da reprodução da vida. Que, na prática tradicional, o conhecimento científico adotado é amalgamado com o conhecimento tradicional e místico-sagrado, originando práticas interculturais de conservação.